Legal Analysis of Supreme Court Decisions on Community Land Compensation: A Case Study of the Jatikarya Toll Road Project - Aprilidya, Tri; Setiadi, Wicipto (Jayapangus Press, 2024)
The Jatikarya Toll Road construction project, part of the Cimanggis-Cibitung Toll Road, aims to improve connectivity and transportation efficiency in the Jabodetabek area. However, the land acquisition process for this project has caused conflict, especially regarding compensation payments that are considered unfair by the affected community. This study aims to analyze legal protection of community rights in the implementation of Supreme Court Decision Number 815/PDT/2018, especially regarding land compensation payments. Using normative legal research methods with a legislative and analytical approach, this study examines the application of agrarian law and regulations related to land acquisition for public interest. The results of the study show that although residents have won the lawsuit at the Supreme Court, the implementation of the legal decision is still constrained by various factors, including government administration and limited legal evidence of land ownership. The consignment mechanism often exacerbates residents' dissatisfaction because it does not optimally involve them in the decision-making process. The imbalance between the need for infrastructure development and the protection of the rights of affected communities reflects the weak implementation of the principle of justice in land acquisition. Therefore, a more inclusive and transparent policy is needed to ensure that people's rights are protected in accordance with applicable laws and regulations.